Qatar's communication strategy and the resolution of the diplomatic conflict in the Gulf - González Santamaría, Ana Isabel (2021)
On the 5th of June 2017, Saudi Arabia, the United Arab Emirates, Egypt and Bahrain announced the rupture of diplomatic relations and the closure of borders with Qatar in response to its alleged support for terrorist activities destabilising the region. In order to revert the situation, 13 demands were made, which Qatar refuses to meet. Qatar was isolated within the Gulf Cooperation Council and its international image was damaged, particularly after the Trump Administration backed the blockade. In these trying circumstances, Qatar has managed to resist by developing a public diplomacy that integrates the analogue and digital environments in which communications play a vital role. Qatar has protested its innocence before regional and international public opinion, and it has denounced the anti-Qatar campaign and fake news stories that flooded social media, particularly Twitter, before and during the first months of the crisis. It has developed a communication strategy showing its willingness to open dialogue, respect for international bodies where it defended its cause, together with diplomatic activities reinforcing its positions before very diverse actors such as the United States, international bodies, Kuwait and Turkey. Qatar used this strategy to transform its online influence into offline diplomatic influence until it succeeded in getting Kuwait to act as mediator, with the support of the United States, in order to put an end to the blockade, which was the top goal of its foreign policy.